Addressees Are Sensitive to the Presence of Gesture When Tracking a Single Referent in Discourse - Debreslioska, Sandra; van de Weijer, Joost; Gullberg, Marianne (Frontiers in Psychology, 2019)
Production studies show that anaphoric reference is bimodal. Speakers can introduce a referent in speech by also using a localizing gesture, assigning a specific locus in space to it. Referring back to that referent, speakers then often accompany a spoken anaphor with a localizing anaphoric gesture (i.e., indicating the same locus). Speakers thus create visual anaphoricity in parallel to the anaphoric process in speech. In the current perception study, we examine whether addressees are sensitive to localizing anaphoric gestures and specifically to the (mis)match between recurrent use of space and spoken anaphora. The results of two reaction time experiments show that, when a single referent is gesturally tracked, addressees are sensitive to the presence of localizing gestures, but not to their spatial congruence. Addressees thus seem to integrate gestural information when processing bimodal anaphora, but their use of locational information in gestures is not obligatory in every discourse context.